2019
DOI: 10.3126/jbpkihs.v2i2.27853
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Clinical Score and Serum Acetylcholinesterase Level as a Predictor of Outcome among Patients with Acute Organophosphate Poisoning Admitted in Emergency Ward of a Tertiary Hospital

Abstract: Background: Monitoring a patient's serum acetylcholinesterase (AChE) status after clinical score of organophosphate poisoning enables the verification of exposure to anticholinesterase agents. Methods: A cross-sectional study was conducted among the patients fulfilling the inclusion criteria and was categorized according to POP (Peradeniya Organophosphorus Poisoning) score. The study was conducted at a tertiary hospital for one year in the period of Jan 2016 to Dec 2016. POP score was applied and serum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Mean serum CK level in males was as elevated as seen in the intermediate phase but the patients were not followed up. 12 Our study has shown that females outnumbered males in organophosphate poisoning as with other studies carried out in Nepal, 2,8 in contrast to the studies done in India which have shown male preponderance. 11,12 Another tissue injury marker, LDH has also been reported to be elevated in organophosphate poisoning in many studies.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Mean serum CK level in males was as elevated as seen in the intermediate phase but the patients were not followed up. 12 Our study has shown that females outnumbered males in organophosphate poisoning as with other studies carried out in Nepal, 2,8 in contrast to the studies done in India which have shown male preponderance. 11,12 Another tissue injury marker, LDH has also been reported to be elevated in organophosphate poisoning in many studies.…”
Section: Discussionsupporting
confidence: 65%
“…7 Predominant cholinergic effects are seen when serum cholinesterase is less than 50% normal range. 8 Few studies have reported a significant positive correlation between CK with the severity of organophosphate poisoning. 5 , 7 , 9 This might be the reason that we found raised serum creatine kinase levels in a higher proportion of cases (94%) in contrast to the studies done in India (24%), 10 and (8%).…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al (2020) stated that out of 80 patients, 29 were classified as mild poisoning, 31 as moderate poisoning, and 20 as severe as per POP scale. Chaudhary et al (2019) reported that out of 100 OPC patients, 57 (57%) were classified as mild, 38 (38%) moderate and five (5%) as severe poisoning. On the other hand, Eisa et al (2021) stated that 61.1% of studied patients had moderate toxicity, 25% had mild toxicity, while 13.9% had severe toxicity according to POP score.…”
Section: Discussionmentioning
confidence: 99%
“…The high survival rate can be explained by early referrals, adequate first aid, early administration of antidotes and oxygen when indicated (Amir et al 2020). Chaudhary et al (2019) had demonstrated that the POP scale is a reliable predictor of the severity of OPC poisoning and that it can access the intensity, morbidity, and mortality of individuals who have been exposed to OPC. Also, Samy et al (2018) revealed the mortality rate was considerably greater in patients with severe poisoning compared to those with moderate poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…Chaudhary R et al [20] concluded that the higher degree of POP score correlated to higher degree of serum acetylcholinesterase derangement, need for atropine, PAM and length of hospital stay. Thus, it enhances in the prediction of outcome among patients with acute organophosphate poisoning.…”
Section: Need Of Atropine and Pralidoximementioning
confidence: 99%